Pemberdayaan Covid-19 melalui Peningkatan Kesadaran Masyarakat dalam Mengikuti Program Vaksinasi - Jaya, Agung Kadarusman Mita; Firdaus, Fawwaz Miftah; Muhtar, Siti Nuraeni (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2022)
Real Work From Home Lectures are a form of student service to the community. The form of community service is to help solve problems that exist in the community. As the spread of COVID-19 increases, vaccination is carried out with the aim of preventing these problems, but there are still many people who do not want to participate in the vaccination program, especially rural communities who swallow information in its entirety without knowing the truth first. Therefore, a socialization activity was held which is one of the efforts to increase public awareness in Pasirloa Hamlet, Kadakajaya Village, Tanjungsari District, Sumedang Regency in participating in the vaccination program. The community empowerment-based service method (SISDAMAS) is realized through outreach activities to the Dusun Pasirloa community who still have low awareness of participating in the vaccination program. As for what is at the core of the socialization, among others: First, Explaining the benefits of vaccines. The benefit of the vaccine itself is to maintain the body's immunity and make the body not easily exposed to COVID-19. Second, Explain the procedure to be carried out before the vaccine dose is injected. The procedure for injecting vaccine doses begins with blood pressure checks, body temperature checks, a question and answer session if the vaccination participant has a congenital disease. If the vaccine participant has passed the inspection stage, the vaccine dose is injected. Third, explain the effects after the vaccine is injected. The effects after the dose of the vaccine are mild fever, muscle aches in the form of aches, headaches and other mild symptoms. Fourth, convince the public and ensure vaccine safety. This process is carried out by explaining that the vaccine has been proven to be safe and its halal has been tested by the MUI.